Alternative Shakespeares - Drakakis, John (New accents (Routledge (Firm)), 2002)
Alternative Shakespeares, published in 1985, shook up the world of Shakespearean studies, demythologising Shakespeare and applying new theories to the study of his work. This book provides an updated analysis of Shakespearean studies.